Gambaran Tingkat Pengetahuan Ibu Hamil Tentang Pencegahan Penularan HIV pada Anak (PPIA) di Puskesmas Putat Jaya Kota Surabaya - Hamidah, Nadhifa Alya; Setyowati, Dewi; Sari, Gadis Meinar (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The proportion of HIV-positive pregnant women in Indonesia rises annually. Pregnant women’s HIV test results in Indonesia fall a little short of the target for 2022. Knowledge is one of the most important aspects of the prevention of mother-to-child transmission of HIV (PMTCT). The aim of this research is to determine the knowledge among pregnant women in Putat Jaya Community Health Care in Surabaya regarding the transmission of HIV from mothers to their children. Cross-sectional analysis is used in this descriptive study. There are 35 pregnant women who have responded. Mothers enrolled in trimesters 1, 2, and 3 who are getting antenatal care at Putat Jaya Community Health Care in Surabaya meet the inclusion criteria for this study. However, a mother with special needs is the sole requirement for this study. In September 2023, this study was carried out at Putat Jaya Community Health Care in Surabaya. The method for gathering samples is called purposive sampling. According to the findings, 77.1% were sufficiently aware of how to prevent HIV transmission from mother to child, followed by 14.3% who had high knowledge and 8.6% who had a lack of knowledge about the prevention of mother-to-child transmission (PMTCT) of HIV.